Low‐dose administration of bleomycin leads to early alterations in lung mechanics. Issue 12 (17th October 2018) - Headley, Lauren; Bi, Weizhen; Wilson, Cory; Collum, Scott D.; Chavez, Melissa; Darwiche, Tamara; Mertens, Tinne C. J.; Hernandez, Adriana M.; Siddiqui, Saad R.; Rosenbaum, Stephanie; Johnston, Richard A.; Karmouty‐Quintana, Harry
Abstract : New Findings: What is the central question of this study? When do alterations in pulmonary mechanics occur following chronic low‐dose administration of bleomycin? What is the main finding and its importance? Remarkably, we report changes in lung mechanics as early as day 7 that corresponded to parameters determined from single‐frequency forced oscillation manoeuvres and pressure–volume loops. These changes preceded substantial histological changes or changes in gene expression levels. These findings are significant to refine drug discovery in idiopathic pulmonary fibrosis, where preclinical studies using lung function parameters would enhance the translational potential of drug candidates where lung function readouts are routinely performed in the clinic. Abstract: Idiopathic pulmonary fibrosis (IPF) is the most widespread form of interstitial lung disease and, currently, there are only limited treatment options available. In preclinical animal models of lung fibrosis, the effectiveness of experimental therapeutics is often deemed successful via reductions in collagen deposition and expression of profibrotic genes in the lung. However, in clinical studies, improvements in lung function are primarily used to gauge the success of therapeutics directed towards IPF. Therefore, we examined whether changes in respiratory system mechanics in the early stages of an experimental model of lung fibrosis can be used to refine drug discovery approaches for IPF. C57BL/6J mice were administered bleomycin (BLM) or a vehicle controli.p . twice a week for 4 weeks. At 7, 14, 21, 28 and 33 days into the BLM treatment regimen, indices of respiratory system mechanics and pressure–volume relationships were measured. Concomitant with these measurements, histological and gene analyses relevant to lung fibrosis were performed. Alterations in respiratory system mechanics and pressure–volume relationships were observed as early as 7 days after the start of BLM administration. Changes in respiratory system mechanics preceded the appearance of histological and molecular indices of lung fibrosis. Administration of BLM leads to early changes in respiratory system mechanics that coincide with the appearance of representative histological and molecular indices of lung fibrosis. Consequently, these data suggest that dampening the early changes in respiratory system mechanics might be used to assess the effectiveness of experimental therapeutics in preclinical animal models of lung fibrosis. Abstract :